2. STUDY THE PREVALENCE OF MALARIA INFECTION IN THE IA HDREH COMMUNE, KRONG PA DISTRICT, GIA LAI PROVINCE IN 2020 (Vietnam Journal of Community Medicine, 2024)
Objectives: Determine the prevalence of malaria parasites and the associated factors with the infection percentage in the Ia Hdreh commune, Krong Pa district, Gia Lai province.Material and method: Cross-sectional study conducted on 406 people living in Ia Hdreh commune, Krong Pa district, Gia Lai province, from October 2019 to June 2020 with malaria testing including species identification and asexual/sexual identification, combined with investigation of epidemiological information.Result: The prevelance of malaria parasite infection in the community of Ia Hdreh commune was 3.2%, the rate of gametocytes accounts for 0.74% of the total 406 people. There was some statistically significant relatives between the rate of malaria parasite infection and age group, education level, and especially bed net sleeping habit (OR 6.24).Conclusion: There is malaria occurence in the community of Ia Hdreh commune with a prevalence of 3.20%; with a gametocyte rate of 0.74%, in which P.falciparum/ P.vivax accounts for 76.90%/23.10%. It is necessary to closely monitor developments in the malaria situation in Ia Hdreh commune, Krong Pa district, Gia Lai province and evaluate the results of implementing intervention to prevent and control malaria to promptly prevent the epidemic from occurring.
Keywords: Malaria, parasite Plasmodium, Gia Lai province, Vietnam.